Tata Cara Perkawinan Adat Amanatun Utara (Timor) Dalam Pelaksanaan Proses“Mafe Mamoen” di Tinjau Dari Undang-Undang Nomor 16 Tahun 2019 di Kabupaten Timor Tengah Selatan - Omri Yori Linome; Reny Masu; A.Resopijani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Overall, Nasi Village can be seen from the topography of the hilly and mountainous area with a height of 726 km and an average rainfall of 15-20% per year. Some of the community's livelihoods are as farmers and livestock breeders with a land area of ​​670 ha/family. East Nusa Tenggara has a variety of cultures, such as traditional ceremonies, which of course differ from one region to another. The main problems in this research are (1) What are the marriage procedures for the North Timor Amanatun traditional tribe and the values ​​contained therein according to Law no. 16 of 2019? (2) What efforts have traditional leaders made to preserve the marriage procedures of the North Timorese Amanatun tribe in accordance with Law no. 16 of 2019? (3) What is the impact of marriages from the Timorese traditional tribe (North Amanatun) which are not in accordance with Law no. 16 of 2019? This research is empirical research, so the data sources used are primary data sources obtained from the field and secondary data sources obtained from the literature. The results of this research show that (1) Traditional marriage procedures in Amanatun are meeting to eat betel nut (mahine or makahina), marriage proposal (Tam Hen Tote), marriage blessing (Leutus), (2) Efforts to preserve traditional marriages in the North Amanatun Tribe (Timor) By maintaining the culture in the village of Nasi, the traditional elders do not allow other cultures to enter the village of Nasi, let alone take part in the implementation of customs. (3) The impact of traditional tribal marriages is that unexpected events occur such as